The short- and long-term effects of student absence: Evidence from Sweden - Sarah Cattan; Daniel A. Kamhöfer; Martin Karlsson; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2017)
Instructional time is seen as an important determinant of school performance, but little is known about the effects of student absence. Combining historical records and administrative data for Swedish individuals born in the 1930s, we examine the impacts of absence in elementary school on short-term academic performance and long-term socio-economic outcomes. Our siblings and individual fixed effects estimates suggest absence has a moderate adverse effect on academic performance. The detrimental effect fades out over time. While absence negatively correlates with final education, income and longevity, we only find robust evidence that it lowers the probability of employment at age 25-30.
Keywords: C23; I14; I21; I26; 330; Absence in school; Educational performance; Long-term effects; Register data